Assessing and mitigating impacts of motorboat noise on nesting damselfish. (November 2020) - McCloskey, Kieran P.; Chapman, Katherine E.; Chapuis, Lucille; McCormick, Mark I.; Radford, Andrew N.; Simpson, Stephen D.
Abstract: Motorboats are a pervasive, growing source of anthropogenic noise in marine environments, with known impacts on fish physiology and behaviour. However, empirical evidence for the disruption of parental care remains scarce and stems predominantly from playback studies. Additionally, there is a paucity of experimental studies examining noise-mitigation strategies. We conducted two field experiments to investigate the effects of noise from real motorboats on the parental-care behaviours of a common coral-reef fish, the Ambon damselfish Pomacentrus amboinensis, which exhibits male-only egg care. When exposed to motorboat noise, we found that males exhibited vigilance behaviour 34% more often and spent 17% more time remaining vigilant, compared to an ambient-sound control. We then investigated nest defence in the presence of an introduced conspecific male intruder, incorporating a third noise treatment of altered motorboat-driving practice that was designed to mitigate noise exposure via speed and distance limitations. The males spent 22% less time interacting with the intruder and 154% more time sheltering during normal motorboat exposure compared to the ambient-sound control, with nest-defence levels in the mitigation treatment equivalent to those in ambient conditions. Our results reveal detrimental impacts of real motorboat noise on some aspects of parental care in fish, and successfully demonstrate the positive effects of an affordable, easily implemented mitigation strategy. We strongly advocate the integration of mitigation strategies into future experiments in this field, and the application of evidence-based policy in our increasingly noisy world. Graphical abstract: Image 1 Highlights: Motorboat noise can disrupt reproductive behaviour in nesting reef fish. Applying acoustic buffer zones effectively lowers noise-exposure levels at nests. Acoustic buffer zones alleviate disruption to defensive acts by nest-guarding males. A zone-based strategy is easy to implement and can mitigate noise impacts on fish. Abstract : Motorboat noise can disrupt reproductive behaviour in nesting reef fish. Applying acoustic buffer zones effectively lowers noise levels at nests, and alleviates disruption to defensive acts by nest-guarding males.